Lived experience of relatives of patients with stroke. - Nyirenda, Tauncio (Kamuzu University of Health Sciences, 2022)
Stroke is the third most common cause of death in industrialized countries and a major cause of adult disability. However, the burden of caring for 1 stroke survivors usually rests with family members who have neither chosen nor volunteered for the role of careers The aim of the study is to find out about the knowledge and experiences of relatives of stroke patients in relation to stroke. This will help to fill in the gaps that exist concerning management of stroke survivor patients, hence improving the lives of these stroke survivor patients. The aim of the study is to find out about the knowledge and experiences of relatives of stroke patients in relation to stroke. This will help to fill in the gaps that exist concerning management of stroke survivor patients, hence improving the lives of these stroke survivor patients. The study will be descriptive in nature, and qualitative research method will be used. Qualitative methodology focuses on individuals' lived experiences as they are presented in thoughts, ideas, feelings, attitudes and perceptions. In addition, the research approach emphasizes human behaviour and social interaction. The general systems theory will be used to guide the study. The study will use a sample of 15 relatives of stroke patients who will accompany their stroke patients to physiotherapy and/or to hypertension clinic at Kamuzu Central Hospital. The subjects will be selected through purposeful sampling. Data which will be collected from this study will be analysed manually. It will be interpreted and illustrated using graphs, tables and diagrams.